Simulation on IPv6 - Mohamad Aminuddin, Maisarah (Universiti Teknologi PETRONAS, 2006)
This report is to have an insight on the final year project of simulation on IPv6. The report explains the background on the current issues that the world is facing with IPv6. Besides that, it states the problem on why this topic has been chosen as a final year project by the student. In this report, the students will also include the results and discussion from the survey that have been conducted. For this project the student will need to construct a simulation ofiPv6 as well as a simple IPv6 test bed. The project will need to have some equipment in order to have the simulation and the test bed. Some literature reviews are presented in order to identify what have others have said or discovered about the topic on IPv6. The literature review will also help the student to have a better understanding on what is needed to be done for the project.